Teachers’ Role Toward Students’ Affective Factors In English Teaching And Learning Process - Hasan, Abdullah (Journal of English and Arabic Language Teaching, 2012)
This paper presents teachers’role toward students’ affective factors in teaching and learning process in the foreign language context. Teachers play crucial roles as facilitators, instructors, advisors and models in English language classroom. Teachers make various efforts to shift the students’ behavior from being unmotivated to be motivated, from being shy to be talkative and self confidence to participate in teaching and learning process.It is evident that teachers’ performance at class will give an influence for their students. The teachers who lack self-esteem will find it difficult to create self-esteem of their students. The teachers who do not lead a warm atmosphere at class will find low spirits of students to learn. So the teachers’ role is very critical and crucial in language teaching.